2021
DOI: 10.1177/14604582211043158
|View full text |Cite
|
Sign up to set email alerts
|

Trend research of vitamin D receptor: Bibliometric analysis

Abstract: Studies on vitamin D receptor (VDR) and its association with multiple disorders are expanding. This bibliometric study aims to find and summarize VDR-related publications, and compare them across various countries, organizations, and journals to demonstrate trends in VDR research. VOSviewer and Excel 2019 were used to classify and summarize Web of Science articles from 1900 to mid-2021. Total records of 8762 articles were analyzed, and maps of co-citations bibliometric keywords co-occurrence were designed. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Our results also suggested that VDR received long-standing attention in immune-related diseases (Figures 6, 7), which was consistent with another bibliometric study on VDR (42). As addressed in the previous section, VDR mediates much known physiological functions of the active form of vitamin D, 1,25(OH) 2 D. Upon binding to 1,25(OH) 2 D, VDR is heterodimerized with the retinoid X receptor in the nucleus, which then combines with the vitamin D-response element (VDRE) in the promoter of the target gene, thereby initiating gene transcription (7).…”
Section: Evolutions and Focuses Of Researchsupporting
confidence: 92%
“…Our results also suggested that VDR received long-standing attention in immune-related diseases (Figures 6, 7), which was consistent with another bibliometric study on VDR (42). As addressed in the previous section, VDR mediates much known physiological functions of the active form of vitamin D, 1,25(OH) 2 D. Upon binding to 1,25(OH) 2 D, VDR is heterodimerized with the retinoid X receptor in the nucleus, which then combines with the vitamin D-response element (VDRE) in the promoter of the target gene, thereby initiating gene transcription (7).…”
Section: Evolutions and Focuses Of Researchsupporting
confidence: 92%
“…The bibliometric method was based on the Clarivate Analytics online subscription database Web of Science™ (WOS) to search the literature. WOS permits a comprehensive investigation of major fields or subfields, as previously reported [ 28 , 29 ]. In this study, we adjusted the document type to “article,” the language to “English,” and the period from 2019 to December 2021.…”
Section: Bibliometric Analysis Methodologymentioning
confidence: 99%
“…Vitamin D levels are negatively correlated with blood sugar, and they are positively associated with insulin resistance. Vitamin defciency in pregnant women with GDM increases the risk of insulin resistance and metabolic syndrome [57,58]. At present, an international consensus has not been reached on the dosage of VD supplementation during pregnancy.…”
Section: Discussionmentioning
confidence: 99%